Takhrīj al-Ḥadīṡ Berbasis Isu: Model Metodologis untuk Membaca Hadis dalam Wacana Keadilan dan Hak Asasi - Sekar Ayu; Filza Syahira; Ananda Maulida; Tsuibatul Aslamiyah Daulay; Idris Siregar (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
Contemporary hadith studies often face methodological challenges in connecting classical hadith texts to modern humanitarian issues, particularly in the discourse of social justice and human rights, without neglecting the scientific rigor of hadith. The classical takhrīj al-Ḥadīṡ approach, which focuses on verifying the sanad and matan, is often considered to not fully address the need for contextual reading of contemporary social dynamics. However, to date, there are still limited methodological models that systematically integrate takhrīj rigor with issue-based analysis. Therefore, this article aims to formulate and test the issue-based takhrīj al-Ḥadīṡ model as an alternative methodological framework in contemporary hadith studies. This study uses a qualitative approach with library research methods. Data were analyzed descriptively and analytically through the stages of issue identification, thematic classification of hadith, sanad and matan analysis, and applied synthesis. The results show that the issue-based takhrīj model is able to systematically map hadith based on specific social problems while maintaining the validity of transmission and consistency of the text’s meaning. The implementation of this model on hadiths about collective responsibility in preventing injustice and the principle of universal compassion demonstrates the relevance of Islamic values in building awareness of social justice and protecting human dignity. In conclusion, the issue-based takhrīj al-Ḥadīṡ model is effective as a methodological approach that bridges the tradition of classical hadith criticism with the need for contextual and applicable hadith readings in addressing contemporary humanitarian challenges.